Pengaruh Citra Merek, Harga dan Promosi terhadap Keputusan Pembelian Produk Sepatu Merek “NIKE” dikota Jepara - Calvary, Theresya; Syahrinullah, Syahrinullah (LPPM Universitas Muhammadiyah Mamuju, 2023)
A company needs to work hard and always innovate in products or services to survive in competition and be able to attract the attention of potential customers who will buy their products. Businesses must know what the expectations and needs of consumers are now or in the future. Compare products with each other, get information either through advertisements or recommendations from the public, and choose to buy. The process by which a buyer purchases or acquires an item is referred to as a product. The number of consumers who buy goods in this study cannot be determined. The research sample was 100 people who were surveyed or buyers who bought Nike shoes in the city of Jepara. A sampling method called purposive was used to give questionnaires to customers in Jepara who buy